Incubation Behavior Differences in Urban and Rural House Wrens, Troglodytes aedon - Heppner, Jennifer J.; Ouyang, Jenny Q. (Frontiers in Ecology and Evolution, 2021)
As global land surfaces are being converted to urban areas at an alarming rate, understanding how individuals respond to urbanization is a key focus for behavioral ecology. As a critical component of avian parental care, incubating adults face a tradeoff between maintaining an optimal thermal environment for the developing embryos while meeting their own energetic demands. Urban habitats are biotically and abiotically different from their rural counterparts, i.e., in food availability, predator compositions, and the thermal environment. Therefore, urban birds may face different incubation challenges than their natural counterparts. We measured incubation behavior of rural and urban house wrens, Troglodytes aedon, with temperature loggers throughout the 12-day period. We found that urban females had more incubation bouts of shorter duration and spent less total time incubating per day than rural females. Results could provide evidence of behavioral shifts of wrens in cities, which have implications for the evolution of parental care. Our findings contribute to our understanding of the behavioral traits needed for city life and possible environmental pressures driving urban adaptations.